Psikoedukasi : Pengenalan Emosi Positif dan Emosi Negatif di SDN Aren Jaya XIV - Apriani Wulandari; Aulia Razanah; Avisha Nur Abidah; Bagus Nuristiyanto; Fajar Aditiya Prasetyo; Oktari Anggi Setya Pratama; Ferdy Muzzamil (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Emotional development in elementary school children is essential to support their social and psychological growth. This community service activity aimed to introduce positive and negative emotions through psychoeducation at SDN Aren Jaya XIV. The methods used included delivering material, emotion card games, matching emotional expressions with daily activities, and reflective games such as emotion-ball. Activities were carried out interactively and adjusted to the students’ developmental level. The results showed that students were able to recognize and express various emotions more accurately. The students participated enthusiastically, and the session ran smoothly. However, the limited time and absence of a quantitative evaluation were noted as constraints in measuring the effectiveness more comprehensively. This activity demonstrates that psychoeducation is a useful approach to enhance emotional awareness in children and should be further developed with more structured planning and evaluation.